Nanosized NiS2-Photosensitized TiO2 Coating on Multi-walled Carbon Nanotubes with Higher Visible Light Photocatalytic Activity - Zhu, Lei; Meng, Ze-Da; Park, Chong-Yeon; Choi, Jong-Geun; Ghosh, Trisha; Oh, Won-Chun (Asian Journal of Chemistry, 2012)
A simple synthesis route to nanoscale NiS2-CNT/TiO2 photocatalyst by a sol-gel method was developed and the visible light photocatalytic activity of the obtained samples for the degradation of methyl orange was studied. The prepared photocatalysts were characterized by XRD, EDX SEM, TEM and BET. For as prepared samples, anatase titanium dioxide and nickel sulfide particles were uniformly deposited on the on the surface of multi-walled carbon nanotubes. The visible light photocatalytic properties were successfully demonstrated by decoloration of methyl orange. The results indicate that the addition of an appropriate amount of multi-walled carbon nanotubes as supports for TiO2 and NiS2 efficiently inhibit the agglomeration of NiS2/TiO2 and extended the light absorption spectrum into the visible region due to the excellent photoelectric characteristics of semiconductor NiS2.